2010
DOI: 10.1002/clc.20667
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between CD40 Gene Polymorphism and Unstable Coronary Atherosclerotic Plaques

Abstract: Background: Recently, CD40 polymorphism was found to be associated with acute coronary syndromes. However, few study was involved in the relationship between CD40 polymorphism and the risk of the vulnerable plaque to rupture so far. Materials and Methods: A total of 699 patients who have received coronary angiography were divided into 3 groups according to the morphological division of the plaques: complex lesions (343 cases), smooth lesions (131 cases), and control group (225 cases).The gene polymorphism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…The CD40 gene (-1C/T) polymorphism has been shown to be associated with vulnerability of atherosclerotic plaques. In a cohort of Chinese patients with CVD the C allele of the gene has been associated with increased risk of plaque rupture (OR 1.7, 95%CI 1.3-2.3) [128]. However, it remains unknown whether a similar effect of these polymorphisms persist in other ethnic cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…The CD40 gene (-1C/T) polymorphism has been shown to be associated with vulnerability of atherosclerotic plaques. In a cohort of Chinese patients with CVD the C allele of the gene has been associated with increased risk of plaque rupture (OR 1.7, 95%CI 1.3-2.3) [128]. However, it remains unknown whether a similar effect of these polymorphisms persist in other ethnic cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence shows that the CD40-CD40L system plays a critical role in atherosclerotic disease progression and plaque destabilization [ 13 ]. Studies showed that polymorphisms in CD40 may influence individuals' susceptibility to the development of cardiovascular events [ 18 , 26 ]. Studies had reported the relationship between rs1883832 at CD40 locus and acute coronary syndrome [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies showed that Apoe À/À /Cd40l À/À mice, as well as anti-CD40L antibody-treated Ldlr À/À or Apoe À/À develop reduced atherosclerosis and/or a plaque phenotype that shows a reduction in inflammation, reminiscent of stable atherosclerotic plaques in humans [18][19][20][21][22][23][24][25][26][27][28][29][30]. The effect of CD40L on atherosclerosis appeared hematopoietic cell-independent, as shown by Cd40l…”
Section: Key Pointsmentioning
confidence: 99%
“…Platelet CD40L is atherogenic, and plays a major role in platelet-leukocyte aggregation and leukocyte recruitment to the endothelium [16]. Expression of CD40(L) in atherosclerotic lesion [22] Increased levels of sCD40L in patients with unstable angina [23] Polymorphisms in CD40 gene correlate with unstable coronary plaques and risk of coronary plaque disruption [24] CD137L CD137 Atherogenic -shown by administration of agonistic antibody against CD137L and Cd137 genetically deficient mice [23,25] Expression of CD137 in atherosclerotic lesion [25] Increased sCD137 levels in patients with ACS [26,27] CD70 CD27 Atherogenic -shown by reduced atherosclerosis in Cd70 À Apoe transgenic mice [28] Expression of CD70 and CD27 on T cells in atherosclerotic lesions [29] OX40L OX40 Atherogenic -shown by administration of neutralizing antibodies to OX40 and Ox40l genetically deficient mice [30,31,32] Increased expression of OX40 in patients with unstable angina…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation